Risk-Based Mining Investment in the Framework of Fair Legal Certainty - Suhartana, Lalu Wira Pria; Asikin, Zainal; Haq, L. Muh. Hayyanul; Azizah, Mabarroh (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
Investment requires a legal system that provides certainty and justice for the community because policy changes are not enough without a market-oriented legal system to attract more investors.This study aims to analyze risk-based mining investment, in order to increase legal certainty in the mining investment sector. The approach used is the legislative, conceptual, and historical approach, by conducting dogmatic, theoretical, and philosophical legal studies. From this study it shows that. The rapid growth of investment flows not only affects the business aspect itself, but also affects the regulatory aspect of the host country. Indonesia's investment policy is driven by several factors such as lack of capital, experience and technology to cultivate economic potential into real economic power, so the use of foreign capital needs to be utilized optimally to accelerate economic development and regions or sectors that cannot be overcome by capital itself. Specifically in the implementation of the mining business, a shift towards a permit-based system is needed to increase regulatory clarity and the need for clarity in the division of authority between the central and regional governments to encourage community involvement in resource management. Mining business permits must be viewed as a preventive instrument aimed at controlling increasingly uncontrolled mining activities, in addition it turns out that mining activities are based on changing policies so that they often cause uncertainty in their implementation.